Envejecer en casa ¿es posible? - Rodríguez Conde, Concepción; Iglesias-Souto, Patricia María; Castro Neo, Mª Jesús; Taboada Ares, Eva María; Puñal Romarís, Mª Elena (Acciones e Investigaciones Sociales, 2011)
Envejecer en casa ¿es posible?